Pengaruh Service Quality Dan Service Value Terhadap Customer Satisfaction Bali Tangi Spa Denpasar - Sri Astiti, Dewa Ayu; Jatra, I Made (E-Jurnal Manajemen, 2014)
Bali Tangi SPA is the best service SPA company which comes from the Bali island. The number of samples obtained by using purposive sampling method is as much as 105 respondents. Based on the analysis we can conclude that the service quality and service value simultaneously significant positive effect of this is evident from the value of F is greater than F table. service quality and service value positive and significant impact on customer satisfaction partially. This can be evidenced from the values of t greater than t table value. Service value is the variable that most affects customer satisfaction at Bali Tangi SPA Denpasar. Key words : service quality , service value